The occurrence of hemorrhagic fever with renal syndrome in southern parts of Bosnia and Herzegovina - Nikolić, Jadranka, liječnica; Kuzman, Ilija; Markotić, Alemka; Đaković-Rode, Oktavija; Curić, Ivo, liječnik; Bebek Ivanković, Helien; Grgić, Svjetlana (2009)
Summary: Bosnia and Herzegovina (B&H) has been known as an endemic region for hemorrhagic fever with renal syndrome (HFRS) for over 50 years. Multiple epidemics of this disease have been registered so far, especially in endemic parts of Central and Northeastern Bosnia, as well as the Sarajevo region. Seroepidemiological investigations demonstrate naturalization of Hantaviruses and their wide spread in B&H. However, there are no studies from the southern areas of B&H, and endemic foci of this disease are unknown. The aim of this study was to determine the distribution and serologic prevalence of Hantavirus infections by testing for specific IgG antibodies against hantaviruses in the population of Herzegovina. This study included two groups of participants. The target group consisted of 300 participants from exposed professional and population groups, and control group included 100 educators with lower exposure to HFRS. Identification of specific IgG antibodies against hantaviruses in 16 participants confirmed an initial assumption about the presence of Hantavirus infections in the region of interest. Seroprevalence of 5% was registered in the »exposed« and 1% in the »unexposed« group. Simultaneous circulation of Puumala (PUU) and Dobrava (DOB) viruses was discovered. The frequency of positive antibody results was higher in the population above 50 years of age, and three times more prevalent in men then at women. The highest proportion of exposed participants (80%) was registered in the municipalities which geographically belong to high or mountainous Herzegovina
Bibliografija: 27 jed
Keywords: Hemoragijska vrućica s bubrežnim sindromom; Bosna i Hercegovina